2015
DOI: 10.4081/idr.2015.5605
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmal upper respiratory infection presenting as leukocytoclastic vasculitis

Abstract: Mycoplasma is a virulent organism that is known to primarily infect the respiratory tract; however, affection of the skin, nervous system, kidneys, heart and bloodstream has been observed in various forms, which include Stevens Johnson syndrome, erythema multiforme, toxic epidermal necrolysis, encephalitis, renal failure, conduction system abnormalities and hemolytic anemia. Small vessel vasculitis is a lesser-known complication of mycoplasma pneumonia infection. We report a case of mycoplasmal upper respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…M. felis is a pleomorphic gram-negative bacterium that causes feline upper respiratory tract infections. According to some studies, mycoplasma is a normal resident of the upper respiratory tract [ 6 , 7 , 8 ], playing a direct or indirect role in conjunctivitis and upper respiratory tract infections [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. felis is a pleomorphic gram-negative bacterium that causes feline upper respiratory tract infections. According to some studies, mycoplasma is a normal resident of the upper respiratory tract [ 6 , 7 , 8 ], playing a direct or indirect role in conjunctivitis and upper respiratory tract infections [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case reports have highlighted intriguing connections between LCV and various comorbidities or triggers. For instance, there have been cases where LCV flares were precipitated by factors such as influenza vaccination, certain infections such as Mycoplasma, and medications such as vancomycin or warfarin [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…LCV case with a history of ischemic heart disease exacerbated by an influenza vaccine, leading to acute renal failure requiring hemodialysis Ippoliti et al [14] LCV occurrence post-heart transplant alongside immunotherapy, indicating a potential link between immunosuppression and vasculitis Rao et al [15] LCV manifestation following Mycoplasma-induced upper respiratory tract superinfection, characterized by conspicuous skin lesions Pingili et al [16] Diffuse LCV and acute renal failure observed after intravenous vancomycin administration, highlighting a medicationtriggered LCV case Elantably et al [17] LCV diagnosis subsequent to warfarin prescription for rheumatic heart disease, exhibiting classic manifestations of LCV Missoum et al [18] Vaccine-induced LCV linked to the inactivated COVID-19 vaccine, diagnosed due to lack of alternative etiology postvaccination Orlando et al [19] LCV coexisting with heart failure showing reduced ejection fraction due to ANCA-negative vasculitides, emphasizing the cardiac implications of vasculitis Golan et al [20] Systemic vasculitis in a patient with Sjögren's syndrome, leading to exertional dyspnea and orthopnea, showing reversibility post-immunosuppressant therapy and improved ejection fraction ANCA: antineutrophil cytoplasmic antibody; LCV: leukocytoclastic vasculitis Among medications, amiodarone has been implicated in vasculitis, specifically LCV, although the exact mechanisms remain less understood [3][4][5]. Current literature suggests the potential involvement of immune complexes formed by amiodarone or its metabolites, triggering an inflammatory response within blood vessel walls, thereby leading to vasculitis [3,4].…”
Section: Study Key Findingsmentioning
confidence: 99%